Fast Food Consumption Patterns and Menstrual Cycle Regularity in Adolescent Girls - Abidah, Siska Nurul; Safitri, Yati Isnaini; Khalimah, Siti (Journal of Health Sciences, 2026)
Adolescence is period important in development, including maturation system marked reproduction with menstruation. Regularity cycle menstruation become indicator health reproduction teenager princess, but still many have experienced irregularity. One of the suspected factors influence condition the is pattern consumption related foods with balance intake nutrition. Objective study This for know connection pattern consumption fast food with regularity cycle menstruation in adolescents daughter. Study use design analytic observational with approach cross sectional. Population includes 45 teenagers daughter at MA Al- Munawwaroh Kembangbahu Lamongan held in the month January- March 2026 with sample of 45 selected respondents through technique total sampling. Variable independent is pattern consumption fast food, whereas variables dependent is regularity cycle menstruation. Instruments in study This use sheet questionnaire FFQ. Data analysis using chi-square test with level significance <0.05. Research result show that part large (33.3%) teenagers daughter is in the category consumption fast food high and partly large (53.3%) teenagers daughter own cycle menstruation abnormal. There is a relationship pattern consumption fast food with regularity cycle menstruation in adolescents daughter at MA Al-Munawwaroh Kembangbahu Lamongan with p-value result 0.000 (p<0.05). Consumption level high fast food potential can influence occurrence irregularity cycle menstruation. Therefore that, it is recommended that teenagers daughter limit consumption fast food and implement pattern eat healthy use guard regularity cycle menstruation.